Peran Guru dalam Pembinaan Akhlak Siswa di SMP Al-Isra Kecamatan Majalaya Kabupaten Karawang - Wahyudin Wahyudin; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (AS-SABIQUN, 2022)
In Islam moral education is very crucial because for that purpose the Prophet SAW was sent. One of the most important components in educating students' morals is the teacher. This paper discusses the role of teachers in moral development at Al-Isra Junior High School, Majalaya District, Karawang Regency. This study uses qualitative methods with observation and interview data collection techniques, as well as data analysis techniques in the form of drawing conclusions. The results of the study concluded that the role of the teacher in fostering the morals of students at Al-Isra Middle School, Majalaya District, Karawang Regency, was threefold, namely the first role of the teacher as a role model in charge of giving examples of noble character to students, secondly the role of the teacher as an educator in charge of providing knowledge and understanding of good morals to students, and the third role of the teacher as a mentor who is in charge of guiding and directing students in learning and religious activities. The supporting factor for the teacher's role in fostering student morals at Al-Isra Junior High School is the collaboration between the principal, teachers, and students as well as school programs that can develop students' potential. The inhibiting factor is student indiscipline.